THE ROLE AND MUTUAL INTEGRATION OF CAD, CAE, AND CAM SYSTEMS IN MECHANICAL ENGINEERING - Yo’ldashev Bilolxon Iqboljon o’g’li, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract The contemporary development of mechanical engineering is inseparable from the  progressive  convergence  of  Computer-Aided  Design  (CAD),  Computer-Aided Engineering (CAE), and Computer-Aided Manufacturing (CAM) into a unified digital environment capable of supporting the full product lifecycle from concept generation to  production  planning,  machining,  inspection,  and  subsequent  optimization.  The scientific and practical relevance of this topic lies in the fact that traditional drawing-based  and  document-fragmented  workflows  no  longer  provide  adequate  speed, traceability, or accuracy for modern manufacturing systems that must operate under conditions  of  mass  customization,  compressed  development  cycles,  rising  quality expectations, and increasing integration between physical and digital production assets. In a model-based enterprise, digital models are not passive geometric representations but  authoritative  information  carriers  that  connect  design  intent,  simulation  data, process  planning,  manufacturing  semantics,  and  quality  assurance.  This  article analyzes the role of CAD, CAE, and CAM systems in mechanical engineering and examines  the  mechanisms,  benefits,  and  constraints  of  their  integration  within contemporary product realization environments. The study is based on a structured analytical  review  of  standards  documents,  NIST  technical  publications,  and  recent scholarly literature on model-based definition, digital thread architectures, CAD-to-CAE  interoperability,  feature  recognition,  process  knowledge  representation,  and digital twin applications in machining. The results show that effective CAD–CAE–CAM  integration  improves  consistency  of  engineering  data,  reduces  design-to-manufacturing  cycle  time,  strengthens  product  quality,  enables  earlier manufacturability assessment, supports more reliable process planning, and provides the informational backbone for digital thread and digital twin implementation. At the same time, the review reveals persistent obstacles, including semantic gaps between design  and  manufacturing  representations,  incomplete  interoperability,  standards implementation  costs,  skills  shortages,  fragmented  knowledge  structures,  and  the continuing coexistence of model-based and drawing-based workflows. It is concluded that the most productive direction for mechanical engineering enterprises is not the isolated  improvement  of  CAD,  CAE,  or  CAM  modules  separately,  but  the establishment  of  model-centric,  standards-based,  and  semantically  rich  integration architectures in which a single authoritative product definition can be reused across design,  analysis,  planning,  machining,  inspection,  and  lifecycle  feedback.  The scientific novelty of the article lies in presenting CAD, CAE, and CAM not as separate software  categories,  but  as  functionally  interdependent  layers  of  a  unified  digital manufacturing logic whose maturity increasingly depends on standards such as STEP AP242, model-based definition, manufacturing feature semantics, and digital thread continuity.  The  practical  significance  of  the  article  lies  in  identifying  a  realistic framework for universities, industrial enterprises, and engineering teams seeking to improve mechanical product development efficiency through deeper CAx integration.